Factors Associated with Cadre Activities In Jember, East Java - Dewi Nofa Wahyuni; Hermanu Joebagyo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Since reformation era in 1998, the activities of the integrated health service post (posyandu) have been declining. In order to revitalize posyandu activities, revitalization strategy was introduced. The purpose of this study was to examine factors associated with posyandu cadre activities in Jember, East Java, including the effectiveness revitalization strategy.Subjects and Method: This was an analytic a cross-sectional study, conducted in Jember, East Java. A sample of 80 integrated health service post (posyandu) cadres was selected for this study. The dependent variable was cadre activity. The independent variables were age, knowledge, education, employment, duration, training, and revitalization strategy. Questionnaire was used to measure variables. Logistic regression was used to analyze data.Results: Duration ≥10 years (OR= 1.53; 95% CI= 0.42 to 5.61; p= 0.524), education ≥high school (OR= 2.35; 95% CI= 0.47 to 11.76; p= 0.299), housewife (OR= 9.58; 95% CI= 1.60 to 57.21; p= 0.013), ever had training (OR= 4.38; 95% CI= 1.21 to 15.77 p= 0.024), good revitalization strategy (OR= 3.71; 95% CI= 1.03 to 13.36; p= 0.045) were associated with increased cadre activity. Age 26-45 years old (OR= 0.35 ; 95% CI= 0.01 to 17.81 p= 0.604), age ≥46 years old (OR= 0.18; 95% CI= 0.01 to 3.66; p= 0.262), low knowledge (OR= 0.80; 95% CI= 0.16 to 4.02; p= 0.786), poor knowledge (OR= 0.40; 95% CI= 0.06 to 2.89; p= 0.367) were associated with decreased cadre activity.Conclusion: Housewife, ever had training, and good revitalization strategy are factors that increase cadre activity, and they are statistically significant. Age 26-45 years old, age ≥46 years old, low knowledge, poor knowledge are associated with decreased cadre activity, but they are not statistically significant.Keywords: cadre activity, cadre characteristic, integrated health service post, revitalization strategyCorrespondence: Dewi Nofa Wahyuni.Masters Program in Family Medicine, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: dewi.nofa86@gmail.com. Mobile: 081330772655.Journal of Health Promotion and Behavior (2017), 2(3): 282-290https://doi.org/10.26911/thejhpb.2017.02.03.08